A COMPARATIVE STUDY OF MEASURING THE ACCURACY OF USING ARTIFICIAL INTELLIGENCE METHODS AS AN ALTERNATIVE TO TRADITIONAL METHODS OF AUDITING (World Economics and Finance Bulletin, 2022)
The purpose of the study is to evaluate two alternative auditing approaches, namely auditing using traditional and recognized ways and auditing using artificial intelligence methods, in order to achieve the very same goals as the audit profession. As a result, it is feasible to take use of artificial intelligence methods' properties such as accuracy, speed, objectivity, and other traits that make their usage vital in auditing. The study is based on an external auditor's opinion on the financial statements of a number of companies over a period of years, as determined by the traditional method of auditing, and an external auditor's conclusion for the same companies over the same period, as determined by one of artificial intelligence applications, which is the artificial neural network.